Molecular studies of Allographa effusosoredica sp. nov. (Graphidaceae) along with its Trentepohlia photobiont and a comprehensive checklist for Indian Allographa - Ansil, Parayelil A.; Rajeshkumar, Kunhiraman C.; Lücking, Robert; O. Paraparath , Sruthi; Sharma, Bharati (Phytotaxa, 2024)
The current study describes a new species, Allographa effusosoredica, from the Western Ghats, India, along with its Trentepohlia photobiont. This study is based on morphological, chemical and molecular analyses using mtSSU, LSU and RPB2 sequence data for Allographa effusosoredica mycobiont and ITS sequence data for Trentepohlia photobiont. Allographa effusosoredica is characterized by a thin effuse thallus with diffuse soredia, 8-spored asci, transversely 7–11 septate ascospores, and norstictic acid chemistry. It is surprisingly similar to the widespread Graphis glaucescens, which differs in the absence of soredia and norstictic acid, but clusters phylogenetically within Allographa, allied to Allographa xanthospora, making the limits between Allographa and the distantly related genus Graphis more diffuse and raising doubts about the correct placement of G. glaucescens. The photobiont of the novel species is allied to Trentepohlia cf. arborum HZ-2017 isolate YN1047. This is the first species of Allographa sequenced from India.